2016
DOI: 10.3390/ma9020101
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten as a Chemically-Stable Electrode Material on Ga-Containing Piezoelectric Substrates Langasite and Catangasite for High-Temperature SAW Devices

Abstract: Thin films of tungsten on piezoelectric substrates La3Ga5SiO14 (LGS) and Ca3TaGa3Si2O14 (CTGS) have been investigated as a potential new electrode material for interdigital transducers for surface acoustic wave-based sensor devices operating at high temperatures up to 800 °C under vacuum conditions. Although LGS is considered to be suitable for high-temperature applications, it undergoes chemical and structural transformation upon vacuum annealing due to diffusion of gallium and oxygen. This can alter the devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…For the application of such sensors at high temperatures, a suitable metallization with a high thermo-mechanical stability, a low electrical resistivity, and a high oxidation and corrosion resistance, as well as a high temperature stable piezoelectric substrate are required. Several metallization systems have been investigated during the last few years concerning their high temperature stability, e.g., Pt-or Ir-based materials [1][2][3][4], oxide dispersion hardened materials [5,6], or refractory metals [7].…”
Section: Introductionmentioning
confidence: 99%
“…For the application of such sensors at high temperatures, a suitable metallization with a high thermo-mechanical stability, a low electrical resistivity, and a high oxidation and corrosion resistance, as well as a high temperature stable piezoelectric substrate are required. Several metallization systems have been investigated during the last few years concerning their high temperature stability, e.g., Pt-or Ir-based materials [1][2][3][4], oxide dispersion hardened materials [5,6], or refractory metals [7].…”
Section: Introductionmentioning
confidence: 99%
“…The major challenge of SAW sensors operating at high temperatures is to prepare stable high temperature film electrodes, since film electrodes such as Pt [7], Pt-Rh [8], Ir-Rh [9], Ru-Al [10], W/Mo [11], W [12], or Pt-Ni/Pt-Zr [13] film electrodes, always undergo rapid agglomeration and recrystallization above 700 °C, resulting in the discontinuity of film electrodes, an increase in resistance, and a failure of the SAW sensor. Until now, many researchers have made much effort to solve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts in recent years have been focused on surface acoustic wave (SAW) sensors [ 1 , 2 ], mainly due to their excellent wireless, passive, small, multifunctional quality, and their ability to be widely applied to systems sensing temperature [ 3 ], pressure [ 4 ], and strain [ 5 ] et al With the progress of science and technology, these SAW sensors, which work in high temperature, harsh environments, are in high demand [ 6 ]. The major challenge of SAW sensors operating at high temperatures is to prepare stable high temperature film electrodes, since film electrodes such as Pt [ 7 ], Pt-Rh [ 8 ], Ir-Rh [ 9 ], Ru-Al [ 10 ], W/Mo [ 11 ], W [ 12 ], or Pt-Ni/Pt-Zr [ 13 ] film electrodes, always undergo rapid agglomeration and recrystallization above 700 °C, resulting in the discontinuity of film electrodes, an increase in resistance, and a failure of the SAW sensor. Until now, many researchers have made much effort to solve this problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taguetta [8] used Ir-Rh alloy electrodes of different compositions and found that Ir-based film electrodes can withstand temperatures as high as 800 °C. Rane [9,10] used tungsten film electrodes to prevent the diffusion of Ga and O atoms from the substrate and obtained stable sensors up to 800 °C. Pereira da Cunha [11] investigated a Pt-Ni/Pt-Zr electrode containing an Al 2 O 3 interfacial layer that was used to reduce the degradation of the electrode layer by inhibiting the interdiffusion and interfacial reactions.…”
Section: Introductionmentioning
confidence: 99%